New snake remains from the Miocene of northern South America - Hsiou, Annie (2010)
We report new snake vertebral remains originating from the late Miocene of south-western Brazilian Amazonia (Solimões Formation) and the middle?late Miocene of Venezuela (Socorro and Urumaco Formations). The Brazilian material was attributed to Boidae (aff. Epicrates sp. and Waincophis sp.) and to two probably undetermined "Colubridae". The new snake vertebrae from Venezuela are referred to the extant boid Eunectes sp.. Known specimens from the middle Miocene of Venezuela (Socorro Formation) are re-evaluated as cf. Eunectes. Until now, South American late Miocene squamate records have been reported only from Argentina and Venezuela. We present the first record in the Neogene of Brazil, considerably increasing our knowledge of the South American herpetofauna.